(untitled) (Global Journal of Human-Social Science, 2012)
Exposure to complex mixtures of air pollutants produces inflammation in the upper and lower respiratory tract Because the nasal cavity is a common portal of entry respiratory and olfactory epithelia are vulnerable targets for toxicological damage The brain is a target for several environmental substances that may or may not be primarily airborne Neurodevelopment and neuro-behaviour largely reflect brain development and its chemically induced modification with resulting delays or deficits in development It is generally believed that the developing brain is a particularly vulnerable target for chemical insult and that such insult may have long lasting or even irreversible developmental consequences Environmental exposures in uterus and during early life may permanently change the body s structure physiology and metabolism and lead to diseases in adult life Infants are particularly vulnerable because of their rapid growth and cell differentiation immaturity of metabolic pathways and development of vital organ systems The central nervous system has unprotected barriers and a broad time window of conformation leading to a long period of vulnerability in the developmental process and to susceptibility to any environmental insult leading to neurological diseases